2017
DOI: 10.1186/s40478-017-0483-z
|View full text |Cite
|
Sign up to set email alerts
|

Lack of chronic neuroinflammation in the absence of focal hemorrhage in a rat model of low-energy blast-induced TBI

Abstract: Blast-related traumatic brain injury (TBI) has been a common cause of injury in the recent conflicts in Iraq and Afghanistan. Blast waves can damage blood vessels, neurons, and glial cells within the brain. Acutely, depending on the blast energy, blast wave duration, and number of exposures, blast waves disrupt the blood-brain barrier, triggering microglial activation and neuroinflammation. Recently, there has been much interest in the role that ongoing neuroinflammation may play in the chronic effects of TBI.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 60 publications
1
21
0
Order By: Relevance
“…Because multiple blast exposures have been common among veterans returning from Iraq and Afghanistan [28], for most studies we used a design in which rats received three 74.5-kPa exposures delivered one exposure per day on 3 consecutive days. In multiple studies using this design we confirmed the lack of neuronal pathology at the light and EM levels as well as the absence of any reactive astrocytosis or general inflammatory reaction [2, 22, 26, 3133] despite the fact that these animals develop chronic PTSD-related behavioral traits [26, 64–67]. Thus based on our experience presented in a number of published studies we believe that these blast pressures mimic a low-level blast exposure equivalent to a human mTBI or subclinical blast exposure.…”
Section: Resultssupporting
confidence: 60%
See 2 more Smart Citations
“…Because multiple blast exposures have been common among veterans returning from Iraq and Afghanistan [28], for most studies we used a design in which rats received three 74.5-kPa exposures delivered one exposure per day on 3 consecutive days. In multiple studies using this design we confirmed the lack of neuronal pathology at the light and EM levels as well as the absence of any reactive astrocytosis or general inflammatory reaction [2, 22, 26, 3133] despite the fact that these animals develop chronic PTSD-related behavioral traits [26, 64–67]. Thus based on our experience presented in a number of published studies we believe that these blast pressures mimic a low-level blast exposure equivalent to a human mTBI or subclinical blast exposure.…”
Section: Resultssupporting
confidence: 60%
“…We have been studying a rat model developed to mimic blast exposures that would be associated with human mTBI or a subclinical exposure, an exposure that we refer to as “low-level” [29]. In multiple studies the lack of generalized neuronal pathology at the light and EM levels has been confirmed as well as the absence of any generalized reactive astrocytosis or inflammatory reaction [2, 22, 26, 3133]. Because multiple blast exposures have been common among veterans returning from Iraq and Afghanistan [28], for most studies including the present we used a design in which rats received three exposures delivered one per day on 3 consecutive days.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to our results, repetitive low-level blast TBI in adult rats did not induce gliosis and overt histopathology in the chronic stages. 44 Indeed, the current study shows that repetitive TBI in adolescent mice can lead to long-term, progressive neurological dysfunction in the absence of significant histopathology. These findings have important implications for adolescents who play contact sports or are otherwise at risk of repetitive head injury, inasmuch as mechanisms other than or in addition to those associated with CTE may be relevant to development of impaired neurological function later in life.…”
Section: Discussionmentioning
confidence: 61%
“…Animal studies used predominately rats ( 45 , 48 51 , 53 57 , 59 62 , 65 , 66 ). Sample sizes in studies using rats ranged from 10 to 180, with 75% of studies including fewer than 100 subjects.…”
Section: Resultsmentioning
confidence: 99%